Changes on the waterfront - transforming harbor areas - Hans Harms (University of California, Institute of Urban and Regional Development (IURD), 2008)
The decline of seaports and the appearance of derelict waterfronts became a topic for discussion, research and urban planning, in the context of local and global restructuring, since the 1960s. The 'waterfront' represents that edge of the port city where water and land meet, where sea transport interchanges with land transport. It was the place, where up to the 1950s, goods in barrels and crates were loaded and unloaded by longshoremen and stored for a while in warehouses; where the bulk of the cargo was broken into parts and sorted, and then distributed to production places for further work to add value to the raw products. Since ancient times, the waterfront was the place where information and news of other places were exchanged, where locals met foreigners and where sailors went looking for entertainment. The concept of the waterfront took on nearly mythical aspects. But all that changed with the appearance of the container, the computer and the internet. The scale of ships and boxes increased enormously and the time required for information transmission from distant places shrunk to nearly zero, made possible by miniaturized chips in computers. The change and the transformation of the waterfront contain two different processes and planning issues: one is to plan the transformation of the traditional port for the requirements of the new age of container ships and container handling, and for the necessary transport infrastructure. The second issue is one of urban planning related to land use changes from former port uses to new urban uses (i.e., urban services, offices, housing, recreation etc.), mostly (after a period of decay and stagnation) with considerable increases in land values. In both cases often conflicting interests and actor groups are involved. The paper presents two case studies and compares the decision making in the two processes and their results in two different planning contexts and cultures in the Bay area in San Francisco and Oakland and in Hamburg, Germany.
Keywords: 330